Neonates with a 10-min Apgar score of zero: Outcomes by gestational age. (October 2019) - Zhong, You Jia; Claveau, Martine; Yoon, Eugene W.; Aziz, Khalid; Singhal, Nalini; Shah, Prakesh S.; Wintermark, Pia; ,; Shah, Prakesh S.; Kanungo, Jaideep; Ting, Joseph; Cieslak, Zenon; et al.
Abstract: Background: The current resuscitation guidelines for neonates recommend considering stopping resuscitation efforts if the heart rate remains undetectable after 10 min of adequate resuscitation. However, this recommendation does not take into account the gestational age (GA) of the neonates. We determined the outcomes of neonates with a 10-min Apgar score of zero (Apgar 10 = 0) with respect to their GA. Methods: In a retrospective matched cohort study, we studied neonates admitted to the Canadian Neonatal Network NICUs between 2010 and 2016 with an Apgar 10 = 0. The neonates were divided into 3 subgroups according to their GA: (1) ≥36 weeks', (2) 32 0/7 –35 6/7 weeks', and (3) <32 weeks'. Each neonate with Apgar 10 = 0 was matched 1:1 with neonates of same GA and sex but Apgar 10 = 1–2 and Apgar 10 = 3–5. Survival and brain injury were compared between matched groups. Results: 177 neonates had Apgar 10 = 0. Survival to discharge was significantly different between GA groups [≥36 weeks' 61% vs. 32 0/7 –35 6/7 weeks' 58% vs. <32 weeks' 35%, p = 0.04]. Survival to discharge was similar to their matched cohort with Apgar 10 = 1–2 for neonates born at ≥36 weeks' (61% vs. 66%) and between 32 0/7 to 35 6/7 weeks' (58% vs. 54%), but significantly different for neonates <32 weeks (35% vs. 61%, p = 0.04). Conclusion: Neonates with Apgar 10 = 0 had different outcomes depending on their GA. Less than half of neonates born at <32 weeks GA survived; however, a majority of neonates born at 32 0/7 –35 6/7 weeks' and ≥36 weeks' GA survived at similar rates than their matched neonates with Apgar 10 = 1–2.